2000
DOI: 10.1007/s004410050057
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic arrangement of SCP b -, FMRFamide-, and histamine-like immunoreactive sensory hair cells in the statocyst of the gastropod mollusc Pleurobranchaea japonica

Abstract: A pair of statocysts are located in the periganglionic connective tissue of the pedal ganglia of the opisthobranch mollusc Pleurobranchaea japonica. Lightand electron-microscopic observations show that the sensory epithelium of the statocyst consists of 13 diskshaped hair cells. Each hair cell sends a single axon to the cerebral ganglion through the static nerve. Neurotransmitters in the hair cells were examined by means of immunocytochemistry. Our results show that the 13 sensory hair cells include two SCPB-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 20 publications
(26 reference statements)
1
16
0
Order By: Relevance
“…5,6), both of which support the validity of the use of the current antiserum for the detection of HA via immunohistochemistry. Moreover, it is known that some of the hair cells in the statocyst are HAergic in the gastropods Aplysia and Pleurobranchaea (Soinila et al, 1990;Ohsuga et al, 2000), which is consistent with our present result (Figs. 1A, 5D, 5E).…”
Section: Discussionsupporting
confidence: 94%
“…5,6), both of which support the validity of the use of the current antiserum for the detection of HA via immunohistochemistry. Moreover, it is known that some of the hair cells in the statocyst are HAergic in the gastropods Aplysia and Pleurobranchaea (Soinila et al, 1990;Ohsuga et al, 2000), which is consistent with our present result (Figs. 1A, 5D, 5E).…”
Section: Discussionsupporting
confidence: 94%
“…Bipolar HA-IR sensory cells have been demonstrated in the epithelial layer of the body wall of both Eisenia and Lumbricus. HA has also been identified in sensory neurons of various peripheral organs of other invertebrates species, such as the statocysts, lip and tentacle of gastropods (Soinila et al 1990;Ohsuga et al 2000;Hegedűs et al 2004) and in the photoreceptor cells of arthropods (Hardie 1987(Hardie , 1988(Hardie , 1989Nässel et al 1988;Pirvola et al 1988). The present study is, however, the first report of the possible simultaneous occurrence of HAcontaining sensory neurons with cell bodies located either at the periphery or in the CNS and suggests the involvement of HAergic efferentation in central networks in two ways: first, as an "internal" member of central network(s) and, second, as peripheral units transmitting sensory information to the members of central network(s).…”
Section: Discussionmentioning
confidence: 99%
“…One large family of peptides known as RFamides (Arg-Phe-NH 2 ) or FMRFamide (Phe-Met-Arg-Phe-NH 2 )-related peptides (FaRPs), are nearly ubiquitous within the Metazoa, in which they have been shown to have a diversity of roles as neurotransmitters, neuromodulators, and neurohormones Greenberg, 1977a, 1989;Bulloch et al, 1988;Lutz et al, 1992;Endo et al, 1995;Di Cosmo and Di Cristo, 1998;Di Cristo and Di Cosmo, 2007). FaRPs have been particularly well studied within gastropod molluscs, including Aplysia, Lymnaea and Helix (Lehman and Price, 1987;Benjamin and Burke, 1994;Suzuki et al, 1997;Oshuga et al, 2000), in which they have been demonstrated to have many functions including regulation of both cardiac and noncardiac muscles, nerves, and glands.…”
mentioning
confidence: 99%